استخلاص و تنقية بروتين سي الفعال و د ا رسة تأثير المعادن و درجة الح ا ررة و الرقم الييدروجيني عمى عممية ارتباطو باضداده المحمولة عمى حبيبات اللاتكس - رشيد, حسن مجيد; ملكونيان, أليس كريكور; عبد الكريم, لينة (Al-Nahrain Journal of Science, 2012)
Nine liters of pleural fluid or Pleural effusion samples were collected from patients suffer from different clinical cases. C-reactive protein was extractcted from the pleural fluid using lecithin and chloroform gave high purity product.The purification of C-reactive protein was carried out by using ion exchange chromatography (DEAE – Sephadex A – 50) and gel filtration (Sephacryl S – 300). The percentage of the recovered C-reactive protein was 35% of the total amount of C-reactive protein characterized with high purity. The purity was confirmed by polyacryl amide gel electrophoresis (PAGE) which revealed one band.The effect of the ions (Mn, Co, Na) used on C-reactive protein showed that the manganese ion activate the reaction between the C-reactive protein and the antibodies bounded on latex. At the contrary, the cobalt ion produced a negative results on the same reaction, whereas the sodium ion showed no effect.The activity of C-reactive protein was within a pH range of 4.5-8 and a temperature ranged of 0-45 ºc.